Relationship between ruminative dispositions and perceived sports performance in young elite athletes in Hong Kong: the role of problem-oriented coping strategies - Chen, Dong-Tai; Nien, Jui-Ti; Geng, Xiaoling; Yu, Jeffrey; Singhnoy, Chatkamon; Chang, Yu-Kai (Frontiers in Sports and Active Living, 2025)
There is a nuanced relationship between rumination and sports performance, which may depend on individuals being predisposed to specific facets of rumination. Additionally, ruminative dispositions are intertwined with coping strategies, with both playing crucial roles in sports performance. This study aimed to investigate the relationships among ruminative dispositions, coping strategies, and sports performance in athletes, considering the perspective of multi-dimensional rumination. This study also examined whether coping strategies are associated with the relationship between ruminative dispositions and perceived sports performance. Parallel mediation analysis was conducted on 111 young elite athletes from the Hong Kong national team to examine the relationships between ruminative dispositions, coping strategies, and sports performance. The results revealed that emotion-focused ruminative disposition (ERD) and meaning-searching ruminative disposition (MRD) were negatively associated with perceived sports performance, with problem-oriented coping (POC) playing a partial role. In contrast, instrumental ruminative disposition (IRD) was positively associated with perceived sports performance, fully via POC. These findings suggest that athletes with higher levels of ERD and MRD tend to use POC less frequently, which was associated with poor perceived sports performance. Conversely, athletes with higher levels of IRD tend to employ POC more frequently, which was positively associated with perceived sports performance. The proposed model provides the theoretical framework for multi-dimensional rumination in sports psychology and outlines the potential impact of coping strategies on athletic performance. Importantly, this research underscores that the outcome of rumination is contingent upon its focus.